An alternative surgical approach to treatment of obstructive urolithiasis in a ram - Helayel, Michel José Sales Abdalla; De Nardi, Andrigo Barboza [UNESP]; Dias, Deborah Penteado Martins [UNESP]; Gomes, Márcio Gianordoli Teixeira; Moron, Sandro Estevan; Bomfim, Adriano Cardoso (University of Veterinary Sciences Brno, 2015)
Urolithiasis is defined as calculi formation into the urinary tract. The aetiology is related to mineral imbalance in the diet and in most cases, successful treatment is achieved only through surgical procedures. Furthermore, the breeding ability could be impaired. This report describes the technique of cranial penile urethrostomy associated with partial penectomy performed for the treatment of urolithiasis in a ram. Although limited to cranial obstructions, this technique is low-costs, only the penile tissues are accessed, general anaesthesia is not required and breeding ability may be preserved.
Keywords: Breeder; Calculi; Small ruminant; Surgery; Urinary tract